Effects of pozzolans on acid resistance of shotcrete for sewer tunnel rehabilitation. Issue 1 (2nd January 2019) - Wu, Linping; Hu, Chaoshi; Liu, Wei Victor
Abstract : This study aims to investigate the use of pozzolans–fly ash (FA), metakaolin (MK), and silica fume (SF)—which can be sourced from local mine waste to improve acid resistance of rehabilitation shotcrete. Cement was replaced with these pozzolanic materials at ratios of 5%, 10%, 20%, and 30% to prepare cylindrical samples. These samples were immersed in sulfuric acids (H2 SO4 ) with various pH for 3 months. Then the mass change and uniaxial compressive strength (UCS) at various immersion ages were monitored as possible indicators of degradation. It was found that FA and SF mixes demonstrated reasonable improvement on acid resistance; of the 13 mixes, 5% SF replacement exhibited the least mass loss after 3 months of immersion. However, optimal percentages with the least UCS change varied depending on the acidity of the immersing acid. Furthermore, the effectiveness of mass change and UCS change was discussed regarding the evaluation of acid resistance.